Effect of Postural Changes, Postprandial Load, N. Vagus Pharmacological Denervation and Cryodenervation on Heart Rate Variability in Rats - Chizh, Nikolai A. (Problems of Cryobiology and Cryomedicine, 2017)
Heart rate variability (HRV) spectral analysis was applied to establish how postural change, accompanied by a change in the central venous pressure are associated with a very low-frequency (VLF)-component of the spectrum. Under postprandial load the total power of HRV spectrum was found out to decrease by 1.9 times due to reducing the very low-frequency component of the spectrum. A statistically significant decrease in the LF/HF ratio from 6.7 down to 4.8 due to an increase in the high-frequency range was noted. After treating the animals with Loperamide and Atropine sulfate, which inhibited a motor-evacuation function of gastrointestinal tract, there was established the effect of digestive system on HRV within the LF and HF ranges. The manifestation rate of HRV changes as a result of nervus vagus cryodenervation was shown to be significantly lower than after pharmacological denervation with Atropine sulfate. The ratio of LF/HF components decreased from 3.4 down to 1.3 due to the augmentation of high-frequency component of the spectrum. The findings demonstrated the parasympathetic nervous system to control all the ranges of spectrum and play a major role in HRV formation. Probl Cryobiol Cryomed 2017; 27(3): 266-278